2021
DOI: 10.7554/elife.60554
|View full text |Cite
|
Sign up to set email alerts
|

Plexin-B2 controls the timing of differentiation and the motility of cerebellar granule neurons

Abstract: Plexin-B2 deletion leads to aberrant lamination of cerebellar granule neurons (CGNs) and Purkinje cells. Although in the cerebellum Plexin-B2 is only expressed by proliferating CGN precursors in the outer external granule layer (oEGL), its function in CGN development is still elusive. Here, we used 3D imaging, in vivo electroporation and live-imaging techniques to study CGN development in novel cerebellum-specific Plxnb2 conditional knockout mice. We show that proliferating CGNs in Plxnb2 mutants not only esca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 98 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…The top enriched gene-pairs included Tnfrsf1b_Grn, Tnfrsf1a_Grn, Spp1_CD44, Plxnb2_Ptn, Gpr37l1_Psap, and Gpr37_Psap (Figs 6 D, E, S4F, G). For example, Plxnb2 is a transmembrane receptor that participates in axon guidance and cell migration in response to semaphorins [ 94 ]. Plxnb2 is induced in injury-activated microglia and macrophages early after SCI and facilitates the formation of concentric rings of microglia and astrocytes around the necrotic core of the lesion in a mouse model of SCI [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…The top enriched gene-pairs included Tnfrsf1b_Grn, Tnfrsf1a_Grn, Spp1_CD44, Plxnb2_Ptn, Gpr37l1_Psap, and Gpr37_Psap (Figs 6 D, E, S4F, G). For example, Plxnb2 is a transmembrane receptor that participates in axon guidance and cell migration in response to semaphorins [ 94 ]. Plxnb2 is induced in injury-activated microglia and macrophages early after SCI and facilitates the formation of concentric rings of microglia and astrocytes around the necrotic core of the lesion in a mouse model of SCI [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…In mice, it is expressed from embryo to adult ( Perälä et al , 2005 ) and plays an essential role in both central and peripheral neural system development, involving neuronal migration, synaptogenesis, and axonal guidance regeneration ( Saha et al , 2012 ; Van Battum et al , 2021 ), or as a receptor of angiogenin ( Yu et al , 2017 ). Most Plxnb2 −/− mouse embryos, especially in the C57BL/6 strain, show cephalic neural tube closure defects, leading to perinatal lethality or abnormal nervous system development ( Deng et al , 2007 ; Van Battum et al , 2021 ). In Family 3, the euploid miscarriage contained a compound heterozygous mutation in PLXNB2 (p.D1573E and p.R463Q).…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation of EVT cell migration and invasion is at least partially involved in RM pathogenesis ( Wang et al , 2021 ). It has been shown that PLXNB2 plays an essential role in regulating cellular migration ( Saha et al , 2012 ; Van Battum et al , 2021 ) and tumor invasion ( Gurrapu et al , 2018 ). Our results showed that PLXNB2 knockdown impaired HTR-8/SVneo cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…A reversion of the direction of migration has been described in a wild‐type context for pontine neurons (Shinohara et al., 2013) and cortical interneurons (Tanaka et al., 2009) that can split and retract their leading process. During their tangential migration, cerebellar granule cells also change their polarity, and can migrate bidirectionally and oscillate between their two processes (Renaud & Chédotal, 2014; Van Battum et al., 2021). Our results show that IO neurons axonal extension and migration can also progress in opposite direction when Robo3 is absent.…”
Section: Discussionmentioning
confidence: 99%